Effect of Distance on Utilization of Health Care Services in Rural Kogi State, Nigeria (2011)
Adequate and equitable distribution of health care facilities in rural areas is critical to human capital development. The study determined factors influencing utilization of health facilities in rural Kogi state, Nigeria. The data for the study were collected from 160 rural households and 60 health care providers from randomly selected rural areas from the four agricultural zones in Kogi state. The indices of accessibility reveal that there is unequal access to modern health facilities in the study area. The multinomial logit was used to analyze the factors influencing the utilization of health facilities in the study area. The result reveals that household size, distance and total cost of seeking health care affect the utilization of government and private hospitals while total cost of seeking health care and the quality of access route affect the use of traditional care. The policy implication arising from this study suggests that distance to improved health facilities and the total cost of seeking health care need to be reduced to enhance accessibility to improved health services by various socio-economic groups in the area.